ByzRev 06.2024.011: Nikolas Bakirtzis – Luca Zavagno (eds), The Routledge Handbook of the Byzantine City.: From Justinian to Mehmet II (ca. 500 – ca. 1500). London: Routledge 2024. - Niewöhner, Philipp (The Byzantine Review, 2024)
Nikolas Bakirtzis – Luca Zavagno (eds), The Routledge Handbook of the Byzantine City. From Justinian to Mehmet II (ca. 500 – ca. 1500). London: Routledge 2024. 508 pp., 115 figs. – ISBN: 978-0-367-19679-0